Hepatolithiasis with biliary ascariasis – a case report - Pilankar, KS (BioMed Central, 2003)
BACKGROUND: Biliary ascariasis is regarded as possible etiological factor for hepatolithiasis. Here we report one case of a patient with hepatolithiasis with biliary ascariasis who developed a liver abscess, which was treated with partial hepatectomy. CASE PRESENTATION: A young adult female presented with epigastric pain and vomiting with repeated attacks of cholangitis. ERCP showed evidence of multiple intrahepatic calculi with the development of abscess in the left lobe of liver. The patient underwent partial hepatectomy and was found to have biliary ascariasis on histology. She was treated with antihelmenthic therapy and has had an uneventful postoperative period of 2 years. CONCLUSION: Biliary ascariasis with hepatolithiasis, although rare, should be considered in endemic countries.